THE STATUS OF CONIFEROUS PLANTS OF NAM NUNG NATURE RESERVE IN DAK NONG PROVINCE - Thi Thu, Nguyen; Thanh Trang, Pham; Thi Tuyen, Phung; Thi Tu Duoc, Tran; Thanh Luong, Hoang (Journal of Forestry Science and Technology, 2018)
In this study, we discovered additionally one species (Cephalotaxus mannii Hook.f.) and one family (Cephalotaxaceae) of coniferous plants for Nam Nung Nature Reserve in Dak Nong province. Therefore, the total of species and family of this area increased to seven and three, respectively (including Cephalotaxus mannii Hook. f., Dacrydium elatum (Roxb.) Wall. ex Hook., Dacrycarpus imbricatus (Blume) de Laub., Podocarpus neriifolius D. Don; Keteleeria evelyniana Mast., Pinus massoniana Lamb., and Pinus merkusii Jungh. & de Vriese. Especially, five species are listed in the IUCN Red as VU (two species) and LC (three species). There is one species listed in the Vietnam Red Data Book (2007) as VU (Keteleeria evelyniana Mast.). In addition, two species are listed in the Decree 32/ND-CP as IIA as Cephalotaxus mannii Hook. f. and Keteleeria evelyniana Mast. Therefore, that species distributed in altitude from 800 m to 1,535 m. These findings will significantly provide scientific data for biodiversity management especially for threatened coniferous plant species in Nam Nung Nature Reserve. Furthermore, the result from our research will promote the further study about biodiversity in this area.